Three Pillars of Welfare State Theory: T.H. Marshall, Karl Polanyi and Alva Myrdal in Defence of the National Welfare State - Holmwood, John (European Journal of Social Theory, 2000)
Current social and political theory is sceptical of the future of welfare states in the face of global markets. Their moral claims, too, have been challenged by the neo-liberal association of market capitalism and individual freedom and by an implicit acceptance of that critique - of the welfare state as bureaucratic - by left-wing commentators. This article offers a defence of the national welfare state as the guarantor of 'complex freedom'. This defence is derived from the theoretical contributions of Marshall, Polanyi and Myrdal and offers a reconsideration of the debate immediately after the second world war over the welfare state and its relevance today. Marshall's concept of social rights has become a familiar part of our own debate, but it is argued that Polanyi provides the rigorous critique of market relationships which is missing, and Myrdal locates gender issues as central to the understanding of welfare state development and women's rights as integral to social rights.
Keywords: economic policy; gender; globalization; government policy; human rights; markets; public welfare; social & economic rights; social rights; welfare; welfare economics